We are unconformed: theoretical investigations to explain haitian hunger: We are unconformed: theoretical investigations to explain haitian hunger - Exime, Ethol; Plein, Clério; Mara Pallú, Nelza (Gestão e Desenvolvimento em Revista, 2022)
The objective of this article is to investigate how the theme of hunger and poverty in Haiti is being discussed in scientific research already carried out theorizing the theme, we adopted as methodological strategy, from a literature review, demarcate the following descriptors: 1) Hunger and poverty in Haiti, 2) Brazilian program Fome Zero, 3) Social programs and 4) Cultural Hunger in the period from August 17 to 23, 2021. We used two databases, of theses and dissertations available online: the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) and the Catálogo de Teses e Dissertações of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). The linguistic technique called skimining was used to read the theses. It is concluded that the analyzed theses did not provide enough theoretical and conceptual indexes about Haitian hunger. It is considered a separate case that deserves dedication, discussion and reflections, besides the ideas of social programs, since these would imply in investments, funds that the government does not have, it is time for another way to understand the root of hunger and poverty in Haiti.